2006
DOI: 10.1007/s00383-006-1844-z
|View full text |Cite
|
Sign up to set email alerts
|

Meckel’s diverticular complications in children: is laparoscopy the order of the day?

Abstract: Meckel's diverticulum (MD), a seemingly innocuous anomaly of the gastrointestinal tract, presents distinctive challenges to a clinician, as it is prone to varied complications that are frequently elusive to diagnosis with conventional diagnostic modalities. This case series illustrates the diverse presentations and advantages of laparoscopic-assisted management of Meckel's diverticular complications in children. Between October 2002 and April 2006, 36 patients (27 males and 9 females) aged 1.5 to 16 years (med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 19 publications
1
49
0
1
Order By: Relevance
“…The most common presentation in the pediatric age group is painless rectal bleeding. In a retrospective study of 71 pediatric patients with diagnosed MD, 55.5% of the patients initially presented with rectal bleeding 5 ; however, this number varies among studies 6,7,8 . In a study of 776 patients, Kusumoto et al found that an accurate preoperative diagnosis was made only in 11% of patients presenting with symptoms other than bleeding, compared to 88% in bleeding patients 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common presentation in the pediatric age group is painless rectal bleeding. In a retrospective study of 71 pediatric patients with diagnosed MD, 55.5% of the patients initially presented with rectal bleeding 5 ; however, this number varies among studies 6,7,8 . In a study of 776 patients, Kusumoto et al found that an accurate preoperative diagnosis was made only in 11% of patients presenting with symptoms other than bleeding, compared to 88% in bleeding patients 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Many of other presenting symptoms, such as abdominal pain and nausea, are non specific and may mimic appendicitis. In one study, 11% of children with complicated MDs were initially diagnosed with appendicitis 6 . Ueberrueck et al found that 5 MDs were found incidentally in a series of 311 appendicectomies performed at one institution over 3 year 10 .…”
Section: Discussionmentioning
confidence: 99%
“…However, laparoscopic procedures were performed in 8 of these case reports ( Table 1 ). There are disadvantages to performing intracorporeal resection of Meckelʼs diverticulum, including leakage of the bowel contents during stapling and incomplete resection of the ectopic gastric mucosa 4,9) . It has been reported that laparoscopic-assisted transumblical extracorporeal resection of the diverticulum is a safe and appropriate procedure for treating Meckelʼs diverticulum 1,4,[9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
“…Meckelʼs diverticulum is a remnant of the bowel component and a mesodiverticular band is a remnant of the vascular component of the omphalomesenteric duct 2) . The incidence of Meckelʼs diverticulum is reported to be 1-3% 3) , and 4-34% of affected patients develops complications 4) .…”
Section: Discussionmentioning
confidence: 99%
“…With the advances in the development of laparoscopic technique in children, the use of laparoscopy in the management of inguinal hernia [5][6][7][8] and complicated Meckel's diverticulum had been reported, respectively [9,10]. We herein report the use of laparoscopy in the management of Littre's hernia in two children.…”
Section: Introductionmentioning
confidence: 95%